Integrating grafting and bio-inputs for sustainable management of root knot nematode, Meloidogyne incognita, in tomato cultivation - Nagachandrabose, Seenivasan; Shanthi, Mookiah; Shanmugam, Sankaran Pagalahalli; Elaiyabharathi, Thiyagarajan; Sharmila, Radhakrishnan; Devrajan, Kandasamy; Manickam, Ravishankar; Srinivasan, Ramasamy (Frontiers in Plant Science, 2025)
IntroductionRoot-knot disease in tomato, caused by Meloidogyne incognita, presents a major challenge to global tomato production. This study explored a sustainable management approach by evaluating host-plant resistance through grafting combined with bio-inputs in farmers’ fields with high natural infestations of M. incognita.MethodsThe commercial F1 hybrid Shivam® tomato was grafted onto bacterial wilt-resistant eggplant rootstocks, EG 203 and TS 03. Two field experiments were conducted with six treatment groups to compare the performance of 'EG 203-tomato' and 'TS 03-tomato' grafts against the non-grafted hybrid tomato, both with and without bio-input applications. The bio-input protocol included soil application of neem cake (250 kg/ha) and soil and seedling drenching at nursery and transplant stages using biocontrol agents (Bacillus subtilis, Trichoderma asperellum, and Purpureocillium lilacinum, each at 5 g/L).ResultsResults indicated that the 'EG 203-tomato' graft demonstrated strong resistance to M. incognita, while the 'TS 03-tomato' graft remained susceptible, akin to the non-grafted Shivam® hybrid. The EG 203-tomato graft treated with the bio-inputs achieved the highest suppression of M. incognita, with reductions of 76.8–77.7% juvenile populations in the soil, 62.0–66.1% in female populations within roots, 73.6–77.3% in egg masses per female, and 38.1–40.0% in eggs per egg mass. This treatment also resulted in the lowest root gall index, measured at 2.0–2.1.DiscussionIn both trial locations, 'EG 203-tomato' graft plants enriched with bio-inputs outperformed the non-grafted tomato in growth and yield metrics, achieving greater plant height (54.6–54.7 cm), leaf count (81.3–84.3 per plant), branch count (3.1–3.7) and fruit yield (10.8–11.5 kg/plant). These findings support the recommendation of EG 203-tomato grafts with bio-input management as an effective large-scale strategy for tomato growers combating M. incognita infestations.